A Bibliometric Review of Technology Application in STEM: Insights for Future Research and Practice - Aldeia, AM Saifullah; Aflahah, St.; Nisa, Khaerun (Universitas Muhammadiyah Surakarta, 2023)
Today, STEM development leads to efforts to implement educational openness, emphasizing transparency and unlimited free access to information and knowledge. Rapid information and communication technology development supports efforts to implement open STEM learning. Through this article, the author has mapped study trends regarding the use of technology in STEM education so that it can become an illustration for future studies. The mapping process in this article is carried out using bibliometric analysis, which focuses on scientific publications, collaborations, and citations. Studies on the use of technology in STEM education from 2017 to 2023 show numbers that fluctuate and tend to decrease. The bibliometric analysis in this article also shows the ASEE Annual Conference and Exposition as the most productive proceedings publishing articles on the use of technology in STEM education, Castro M as the most productive author, San Francisco University as the most productive affiliate, United States as the most productive country, and articles compiled by Ibanez with the title Augmented Reality for STEM Learning: A Systematic Review became the most cited articles. This information can be used as a reference for future researchers who wish to study more about the use of information technology in STEM education. Another critical aspect that researchers need to pay attention to if they want to carry out further studies are topics or issues currently popularly associated with using technology in STEM education. Limitations in this article can be completed through further research on the same theme. Future research can include book chapters as a source of metadata. The publication time span can also be added to enrich the analyzed articles.